An Analysis of English Article Errors and Pedagogical Implications in Students’ Writing Skill - Puspita; Suswanto (Poltanesa, 2023)
The study aimed at analyzing a comprehensive account of the dominant type of article errors, finding out the causes of errors, and determining appropriate pedagogical approaches to reduce the errors in students’ descriptive writing tasks. The analysis was based on the Surface Structure Taxonomies of errors comprising omission, addition, and substitution. The data were collected from written samples encountered by 40 first-semester students of Plantation Management, Samarinda State Polytechnic of Agriculture. One of five different topics should be chosen and written by the student in approximately forty-five minutes. The study’s results revealed three types of English article errors that emerged in students’ writing involving omission as the dominant English article error type, addition, and substitution as the second and the third one. The cause of errors emerging in the students’ writing was the first language interference (Indonesian) that strongly influences the process of foreign language (English) acquisition of the articles due to the differences in rules between Indonesian and English structures. Pedagogical implications included a contrastive comparison between languages that may improve learners' ability to instantly recognize differences in article usage between their language systems, conducting simple writing tasks as routine exercises for students, error correction in a flexible way, providing English reading materials and encouraging learners to read the materials extensively.